Change in haematological and selected biochemical parameters measured in feline blood donors and feline whole blood donated units. Issue 4 (April 2017) - Spada, Eva; Proverbio, Daniela; Baggiani, Luciana; Bagnagatti De Giorgi, Giada; Ferro, Elisabetta; Perego, Roberto
Objectives: The quality of whole blood (WB) units is influenced by many factors, starting with selection of donors and the method of blood collection. The aim of this study was to investigate the changes that occur in haematological and selected biochemical parameters in blood transferred from a feline blood donor to feline WB unit. Methods: Data from 27 feline blood donations were used in this study. Cats were anaesthetised with a combination of tiletamine and zolazepam. Blood (10 ml/kg body weight to a maximum of 60 ml/cat) was collected in citrate–phosphate–dextrose–adenine (CPDA) anticoagulant. Lactated Ringer's solution (10 ml/kg) was administered intravenously starting halfway through the donation. Haematological and selected biochemical parameters (complete blood count, free haemoglobin, % haemolysis, glucose, sodium, potassium, pH) were measured in the blood donor before donation and in the corresponding donated WB unit soon after collection. Results: Significant decreases occurred between blood donor and WB unit in red blood cells (mean difference −1.06 × 10 12 /l; P <0.0001), haemoglobin (mean difference −1.6 g/dl; P <0.0001), haematocrit (mean difference −4.6%; P <0.0001), red cell distribution width (mean difference −0.9%; P = 0.0003), white blood cells (mean difference −2.17 × 10 9 /l; P <0.0001), pH (mean difference −0.5; P <0.0001) and potassium (mean difference −1.4 mmol/l; P <0.0001). Significant increases occurred between blood donor and WB unit in platelets (mean difference +87.00 ×10 9 /l; P = 0.0039), glucose (mean difference +25.42 mmol/l; P <0.0001) and sodium (mean difference +20 mmol/l; P <0.0001). Conclusions and relevance: When using a blood collection protocol with intravenous fluid administration midway through the donation and a CPDA:blood ratio of 1:7, there were significant changes in both the haematological and biochemical characteristics between the blood donors and WB units. The majority of these changes may be the result of the anticoagulants used for storage. Understanding these changes may assist selection of blood donors and help prediction of the characteristics of the donated WB unit.